2021
DOI: 10.1007/s40615-021-01080-x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Associations Between Race, Ethnicity, and Past Experiences of Discrimination with Medical Mistrust and COVID-19 Protective Strategies

Abstract: This study investigates the associations between three forms of discrimination, race and ethnicity, general medical mistrust, health-specific COVID-19 conspiracy beliefs, and adherence to COVID-19 protective behaviors. Participants ( n = 963) completed an online survey during May 2020, when stay-at-home orders and other government mandates were implemented in many states. Results indicate that everyday discrimination and healthcare discrimination were associated with significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 79 publications
0
31
0
Order By: Relevance
“…We found that increases in per capita income were associated with decreases in COVID-19 vaccination rates in counties with higher proportions of BIPOC adults. It is plausible that race-based political ideology, unequal health care resource distribution, lack of culture-sensitive public health policies, medical distrust, and contemporary healthcare discrimination may contribute to this negative association between per capita income and COVID-19 vaccination rates in counties with higher proportions of BIPOC adults [19,20,[31][32][33][34]. More studies are needed to explore reasons why COVID-19 vaccination rates in counties with higher proportions of BIPOC adults decrease with increasing per capita income.…”
Section: Discussionmentioning
confidence: 99%
“…We found that increases in per capita income were associated with decreases in COVID-19 vaccination rates in counties with higher proportions of BIPOC adults. It is plausible that race-based political ideology, unequal health care resource distribution, lack of culture-sensitive public health policies, medical distrust, and contemporary healthcare discrimination may contribute to this negative association between per capita income and COVID-19 vaccination rates in counties with higher proportions of BIPOC adults [19,20,[31][32][33][34]. More studies are needed to explore reasons why COVID-19 vaccination rates in counties with higher proportions of BIPOC adults decrease with increasing per capita income.…”
Section: Discussionmentioning
confidence: 99%
“…The deliberate inclusion of community advisory boards such as the NAC ensures the effectiveness of evidence-based interventions in public health emergencies and the increased uptake of COVID-19 testing and vaccination among underresourced and historically marginalized communities who may be distrustful of government and health institutions, 23 and vulnerable to COVID-19 misinformation. 24 …”
Section: Role Of Cbos In Bolstering Asian American Community Healthmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f 6 Sustained investment in effective messaging, transparency, time to process, and workforce development are critical to successfully vaccinating transplant patients. For example, although in the early phases of the pandemic vaccine uptake among persons identifying as Black or Latinx had lagged behind White Americans (largely owing to structural inequalities), 14,15 improved access, time, and outreach by trusted sources have narrowed disparities significantly. Some studies suggest that Black Americans are twice as likely to trust a COVID information when care is race-concordant.…”
Section: What Obligations Do Vaccine Mandates Impose On Transplant Ce...mentioning
confidence: 99%